2013
DOI: 10.1186/1472-6882-13-95
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antidermatophytic activity of the dichloromethane-methanol (1:1 v/v) extract from the stem bark of Polyscias fulva Hiern (Araliaceae)

Abstract: BackgroundDuring the last decades, the number of people suffering from dermatophytoses has seriously increased, mainly due to the development of resistant strains of microorganisms to a range of formally efficient antibiotics. Polyscias fulva, a medium size tree which grows in the West Region of Cameroon is traditionally used for local application against dermatoses and orally against venereal infections. The dichloromethane-methanol (1:1 v/v) extract from the stem bark of Polyscias fulva was evaluated for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The broad range antidermatophytic activities of the isolated compounds from P. fulvia explains the relatively good in vitro and in vivo antidermatophytic activity of the oil-moistened dichloromethane-methanol (1:1 v/v) crude extract from this plant [ 6 ]. They can then serve as markers for the standardization of antidermatophytic phytomedicine from P. fulva .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad range antidermatophytic activities of the isolated compounds from P. fulvia explains the relatively good in vitro and in vivo antidermatophytic activity of the oil-moistened dichloromethane-methanol (1:1 v/v) crude extract from this plant [ 6 ]. They can then serve as markers for the standardization of antidermatophytic phytomedicine from P. fulva .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the dichloromethane extract from the bark of Polyscias fulva appeared to possess a weak antiplasmodial against Plasmodium falciparum (IC 50 = 9.8 μg/ml) and antitrypanosomial activities against Trypanosoma rhodesiense (MIC = 100 μg/ml) [ 5 ]. Furthermore, its dichloromethane-methanol (1:1 v/v) extract showed interesting in vitro and in vivo antidermatophytic properties [ 6 ]. With the aim of producing a standardized phytomedicine from the plant species, the dichloromethane-methanol of the stem bark was fractionated to isolate and characterize the antifungal active principles.…”
Section: Introductionmentioning
confidence: 99%
“…Some biological activities of Polyscias fulva have been reported. In our previous studies, the dichloromethane-methanol (1:1 v/v) crude extract showed interesting antidermatophytic activities both in vitro and in vivo [8]. A number of biologically active (against fungi) compounds have been isolated from P. fulva including two phenolics, one steroid, one triterpene and seven terpenoid saponins [9].…”
Section: Introductionmentioning
confidence: 99%
“…Former phytochemical screening showed that P. alliacea contains substances with proven antifungal activity such as triterpenes, derived alkaloids, flavonoids and saponins [25]. These metabolites probably act by inhibiting the biosynthesis of ergosterol or other sterols present in the fungal membrane, damaging and altering its permeability resulting in loss of essential intracellular elements [26,27]. Especially the saponins are able to form pores in the lipid membrane, to increase cell permeability and inhibit biofilm formation, rendering fungal cells more susceptible to osmotic stress [28,29].…”
Section: Resultsmentioning
confidence: 99%